Status of blue sheep and Himalayan tahr in Dhorpatan Hunting Reserve, Nepal - Karki, JB; Thapa, BB (Banko Janakari, 2013)
A survey of blue sheep (Pseudois nayaur) was conducted in six blocks of Dhorpatan Hunting Reserve (DHR), Nepal. A total of 852 blue sheep were recorded in 73 different groups. The average group size was found to be 11.7 individuals. The average population density of blue sheep in the reserve was found to be 1.28 animals per km2. There were 263 rams, 307 ewes, 89 yearlings and 39 lambs. Among the rams, 126 were classified as trophy rams, 92 as medium rams and 45 as young rams. The ratio of trophy rams to other rams was found to be higher than those found in the earlier studies. The mean sex ratio was 86 males per 100 females and the yearling to ewes ratio was 29 per 100 ewes. The survey of Himalayan tahr (Hemitragus jemlahicus) in Sundaha block recorded 53 individuals with 30 males, 14 females, eight yearlings, and one lamb. The results indicated that the existing quota of blue sheep hunting can be safely continued. In case of higher demands, two more quotas can be added to Barse, Dogadi and Sundaha blocks for the next five years (2008-2012). Himalayan tahrs can be hunted in all the blocks. Sundaha block can sustain four while the rest of the blocks can sustain two Himalayan tahrs per year. DOI: http://dx.doi.org/10.3126/banko.v21i1.9060 Banko Janakari, Vol. 21, No. 1 2011; 25-30